Disparities in Obesity Prevalence in Iranian Adults: Cross-Sectional Study Using Data from the 2016 STEPS Survey - Amin, Rozhin (Obes Facts, 2021)
INTRODUCTION: This paper outlines the prevalence, disparities, and social determinants of preobesity and obesity in Iranian adults. METHODS: Data on 28,321 adults who participated in the 2016 National Survey of the Risk Factors of Noncommunicable Diseases (STEPS) survey were analyzed. The body mass index (BMI) was calculated from physically measured height and weight. To assess the association between sociodemographic factors and the prevalence of preobesity and obesity, a χ2 test and a logistic regression model were used. Socioeconomic inequality was quantified by a concentration index. Disparities in provincial mean BMI and concentration indices were shown on the map of Iran using geographic information system analysis. RESULTS: Overall, 60.3% of the participants were affected by preobesity or obesity. The preobesity prevalence was 39% in men and 35.2% in women. The obesity prevalence was 15.6% in men and 30.4% in women. The mean BMI for the country was 26.5. Higher ranges were observed across the northwestern and central territories. Female individuals in the age group 48–57 years who were married and lived in urban settings had an increased risk of being preobese or obese. The concentration index revealed a prorich inequality, with a greater magnitude among women. CONCLUSION: The findings suggest that policies aimed at reducing preobesity and obesity should remain a public health priority in Iran. However, a greater emphasis should be placed on the northwestern and central territories and on higher socioeconomic groups.